Historical Redlining, Socioeconomic Distress, and Risk of Heart Failure Among Medicare Beneficiaries - Mentias, Amgad; Mujahid, Mahasin S; Sumarsono, Andrew; Nelson, Robert K; Madron, Justin M; Powell-Wiley, Tiffany M; Essien, Utibe R; Keshvani, Neil; Girotra, Saket; Morris, Alanna A; Sims, Mario; Capers, 4th, Quinn; et al. (Circulation (New York, N.Y.), 2023)
The association of historical redlining policies, a marker of structural racism, with contemporary heart failure (HF) risk among White and Black individuals is not well established. We aimed to evaluate the association of redlining with the risk of HF among White and Black Medicare beneficiaries. Zip code-level redlining was determined by the proportion of historically redlined areas using the Mapping Inequality Project within each zip code. The association between higher zip code redlining proportion (quartile 4 versus quartiles 1-3) and HF risk were assessed separately among White and Black Medicare beneficiaries using generalized linear mixed models adjusted for potential confounders, including measures of the zip code-level Social Deprivation Index. A total of 2 388 955 Medicare beneficiaries (Black n=801 452; White n=1 587 503; mean age, 71 years; men, 44.6%) were included. Among Black beneficiaries, living in zip codes with higher redlining proportion (quartile 4 versus quartiles 1-3) was associated with increased risk of HF after adjusting for age, sex, and comorbidities (risk ratio, 1.08 [95% CI, 1.04-1.12]; <0.001). This association remained significant after further adjustment for area-level Social Deprivation Index (risk ratio, 1.04 [95% CI, 1.002-1.08]; =0.04). A significant interaction was observed between redlining proportion and Social Deprivation Index ( <0.01) such that higher redlining proportion was significantly associated with HF risk only among socioeconomically distressed regions (above the median Social Deprivation Index). Among White beneficiaries, redlining was associated with a lower risk of HF after adjustment for age, sex, and comorbidities (risk ratio, 0.94 [95% CI, 0.89-0.99]; =0.02). Historical redlining is associated with an increased risk of HF among Black patients. Contemporary zip code-level social determinants of health modify the relationship between redlining and HF risk, with the strongest relationship between redlining and HF observed in the most socioeconomically disadvantaged communities.